Teaching English Language through ‘Langauge Immersed Science’ for Secondary Classes - K V, Faisal (JOURNAL OF INDIAN EDUCATION, 2022)
This study endeavours to investigate the effectiveness of ‘Language Immersion Programme’ in our classrooms with respect to physics. It is taken for granted that learners from science background are less eloquent and not much confident in verbal expressions. In order to help physics learners master English language effortlessly, an immersion module has been prepared, validated and tried out in class IX in the schools of Kerala. ‘Immerse’ means to dip in water. Here the study is done as to how the elements of English language can be dipped into the subjects to be learned by preparing a package and making a tryout of the same. As taking all the disciplines for the package is beyond the purview of research, the representative items were selected. The study reveals that the package is highly useful and effective. After going through ten sessions of the package, they are reported to be highly confident in using affluent language with creative touch and texture.